Harvesting rice’s dispensable genome - Wing, Rod A. (Genome Biol, 2015)
A rapid and cost-effective approach has been developed to harvest and map the dispensable genome, that is, population-level natural sequence variation within a species that is not present in static genome assemblies. See related Research article: http://www.genomebiology.com/2015/16/1/187.